A influ??ncia da cultura organizacional, por meio dos valores compartilhados, sobre os processos de gest??o de uma empresa de m??dio porte - Ventura, Valmir Alves (2011)
The aim of this work is to identify how the organizational culture, through shared values, it influences the processes of management, acting as limiters or facilitators factors of business development of a medium-sized company. The study was done by analyzing the expression of culture, through shared values, management processes of the organization, within the socioeconomic context and of organizational history. Our approach is rooted in anthropology, using the functionalist perspective of Schein (1984) about organizational culture, which defines it as a dynamic phenomenon of three layers, consisting of surface artifacts, shared values and beliefs. The research method was primarily inductive, qualitative techniques of participant observation, combined with interviews, semi structured, ethnographic and focus interviews, with analysis of critical periods using the ATLAS.ti software. Based on the theoretical background and methodology, this study mapped initially shared values in the organizational culture of a mid-sized trading company in the energy sector, with four units, with its headquarters in the Greater Sao Paulo, and later we identified how these values act as limiters or facilitators organizational development. One contribution of this study is the better understanding above the complexity of influence of shared values that act as limiters factors or facilitators of the management processes, specifically in small and medium enterprises. Besides contributing to the understanding of these values, this research creates a better understanding of organizational culture as a whole. The results identified a dynamic equilibrium with three shared values that act as a backdrop in the organization. These values are composed of various cultural aspects, and while some of these issues act as limiters factors of organizational development, not being fully shared and not having the same degree of importance for its different members, other aspects, which are fully shared and aligned with the organizational strategy, positively influence the management processes, assisting in the implementation of improvements and the use of organizational resources, thus contributing to its growth and acting as facilitators of the organization development. We note that the shared values of characteristics come from the founders, as a culture of quality implemented over a period of four years, although they have been shaped by the context and the sum of experiences shared by all members of the organization. The values were named as efficacy, family environment and professionalism. Identified in the dynamics, there is a balance between three factors: management processes, shared values of organizational culture and strategy of the organization. The management processes are adopted and implemented in accordance with the strategic direction, but are modeled on the shared values, because, like most of these values are implied, the adaptation of processes occurs so often not consciously perceived by members of organization. The three factors keep the balance with a tolerance within the sharing of values. The dynamic balance for itself identifies aspects "strangers" who are outside the tolerance limit the sharing of values. These strange aspects generate discomfort in the organization's members, who create actions to change them, mold them or keep them, suitable to the interests of this dynamic. This happens partly deliberate way, when the processes and strategies are shaped by shared values, or emergent form, when the solutions that emerged between members of the organization are set to shared values, and are accepted by all. Already aspects outside that range, although partially shared, act as constraints of organizational development